2023
DOI: 10.1002/cptc.202300015
|View full text |Cite
|
Sign up to set email alerts
|

Circularly Polarized Luminescent Bis(Boron Difluoride) Complexes with Chiral Schiff‐base Ligands

Abstract: What prompted you to investigate this topic/problem? Small organic CPL-active molecules (CPL-SOMs) have attracted considerable attention in the last decade for their potential application in next-generation optical devices. Our group is investigating CPL-SOMs with chiral Schiff-base ligands, and recently reported that boron difluoride complexes exhibit efficient and tunable CPL properties. [1,2] These findings prompted us to clarify two questions: (1) How do the molecular structures affect the CPL properties; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…As part of our research for the creation of highly fluorescent materials, we recently reported that mono- 14,18,19 and dinuclear 20 boron difluoride complexes exhibited efficient photoluminescence even in the aggregated state. Furthermore, we have achieved lowering the melting point of a boron difluoride complex by introducing polyethylene glycol (PEG) chains into the aromatic rings of Schiff-base ligands, and have succeeded in demonstrating CPL in the solvent-free liquid state.…”
Section: Introductionmentioning
confidence: 99%
“…As part of our research for the creation of highly fluorescent materials, we recently reported that mono- 14,18,19 and dinuclear 20 boron difluoride complexes exhibited efficient photoluminescence even in the aggregated state. Furthermore, we have achieved lowering the melting point of a boron difluoride complex by introducing polyethylene glycol (PEG) chains into the aromatic rings of Schiff-base ligands, and have succeeded in demonstrating CPL in the solvent-free liquid state.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Square planar platinum(II) complexes are widely known for their highly efficient phosphorescent emission, and CPP materials have been created by introducing chiral ligands. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] Several chiral platinum(II) complexes have been reported to show CPP with large dissymmetry factors (g lum = 2DI/I = 2(I L À I R )/(I L + I R )) 18 in the aggregated state. 7,8,12,16 In particular, the co-assembly of achiral and chiral platinum complexes reported by You and coworkers showed a considerably large g lum value of 0.064 from a magnetically-allowed metal-metal-to-ligand charge transfer (MMLCT) transition.…”
mentioning
confidence: 99%
“…8 However, in the solution-dispersed state, the CPP intensities are low for most of the platinum(II) complexes, usually on the order of 10 À3 . 6,9,[12][13][14][15] This is because platinum complexes usually exhibit magnetically-forbidden metal-to-ligand charge transfer (MLCT)derived phosphorescence.…”
mentioning
confidence: 99%
See 2 more Smart Citations